Oil Spillage in Nigeria’s Upstream Petroleum Sector: Beyond the Legal Frameworks - Olujobi, Olusola J.; Oyewunmi, Olabode A.; Oyewunmi, Adebukola E. (International Journal of Energy Economics and Policy, 2018)
The adoption of a broad based sustainable development strategy, underpinned by prudent management of oil resources, coupled with an enduring model for conservation of the natural environment, is an imperative for the Nigerian State. Thus, the paper identifies specific gaps in Nigeria’s environmental legal frameworks and shares critical international perspectives. The study entailed a descriptive legal analysis and utilizes relevant secondary sources. The paper opined that majority of oil spills in Nigeria are not usually addressed in the light of obtainable best practices, inspite of the negative environmental, health and socio-economic consequences. It emphasizes the government’s overarching obligation to enforce applicable environmental laws and regulations. Also captured, is the corresponding responsibility of oil operators to ensure due compliance with their corporate obligations and by implication contributing to the achievement of fundamental environmental protection benchmarks. The paper recommends a holistic reform of relevant laws on the integral oil spillage subject matter. Keywords: Oil spillage, law, environment, Nigeria JEL Classifications: K2, Q4, Q5